Valentine's Day is-- - Gibbons, Gail (Holiday House, 2006)
The history of the holiday and all its fun festivities are presented in this easy-to-read tale filled with Valentine cards, candy hearts, flowers, and full-color illustrations. Valentine's Day is candy hearts, flowers, and chocolate truffles. It is Valentine cards galore. Most of all, it is a time to share with family and friends, and a time to give thanks for our loved ones. Gail Gibbons presents the history of this special holiday and shares what the day has come to mean in our society today.